Pengaruh Kombinasi Birting Ball Dan Aromaterapi Lavender Terhadap Nyeri Punggung Ibu Hamil Trimester III - Ita Mayasari; Nella Vallen IP; Resa Nirmala Jona (Corona: Jurnal Ilmu Kesehatan Umum, Psikolog, Keperawatan dan Kebidanan, 2024)
Back pain is an inconvenience found in pregnant women, especially trimester III pregnant women. Back pain becomes a common problem for pregnant women and could make them feel anxious, afraid, and stressed. The birthing ball and lavender aromatherapy combination is a non-pharmacological therapy and simple physical therapy with the ball. This research determined the combination of birthing ball and lavender aromatherapy combination toward the backpain of trimester III pregnant women at an Obstetrician Practice Erta Faulina Semarang. This pre-experimental research used a one-group-pretest post-test design. The population consisted of all trimester III pregnant women at OB Erna Faulina Semarang. The researchers took 36 samples with purposive sampling. The instruments were a questionnaire and pain observation sheet. Then, the researchers used the Wilcoxon statistic test. The result showed the pain scale before implementing the combination was 5, moderate pain; after the implementation of a combined birthing ball and lavender aromatherapy, the pain scale relieved into 2, mild pain. The Wilcoxon test showed a p-value lower than < α (0,05). The result accepts Ha, indicating the influence of combined birthing ball and lavender aromatherapy on the back pain of trimester III pregnant women. The researcher recommends obstetricians provide the combined birthing ball and lavender aromatherapy for trimester III pregnant women with back pain. This research result could be a reference and insight for students of obstetrics and be an effective obstetric intervention to relieve the backpain of trimester III pregnant women.